Effects of computer-aided rowing exercise systems on improving muscle strength and function in older adults with mild knee osteoarthritis: a randomized controlled clinical trial - Lin, Pei-Ling; Yu, Lee-Fen; Kuo, Shu-Fen; Wang, Xin-Miao; Lu, Liang-Hsuan; Lin, Chueh-Ho (BMC geriatrics, 2022)
Background Osteoarthritis (OA) is common in aged adults and can result in muscle weakness and function limitations in lower limbs. Knee OA affects the quality of life in the elderly. Technology-supported feedback to achieve lower impact on knee joints and individualized exercise could benefit elderly patients with knee OA. Herein, a computer-aided feedback rowing exercise system is proposed, and its effects on improving muscle strength, health conditions, and knee functions of older adults with mild knee OA were investigated. Methods Thirty-eight older adults with mild knee OA and satisfying the American College of Rheumatology (ACR) clinical criteria participated in this randomized controlled clinical trial. Each subject was randomly assigned to a computer-aided rowing exercise (CRE) group (n = 20) or a control group (CON) (n = 18) that received regular resistance exercise programs two times per week for 12 weeks. Outcome measurements, including the Western Ontario and MacMaster Universities (WOMAC), muscle strength and functional fitness of the lower limbs, were evaluated before and after the intervention. Results Participants' functional fitness in the CRE group exhibited significantly higher adjusted mean post-tests scores, including the WOMAC (p = 0.006), hip abductors strength (kg) (MD = 2.36 [1.28, 3.44], p = 5.67 x 10.sup.-5), hip adductors strength (MD = 3.04 [1.38, 4.69], p = 0.001), hip flexors strength (MD = 4.01 [2.24, 5.78], p = 6.46 x 10.sup.-5), hip extensors strength (MD = 2.88 [1.64, 4.12], p = 4.43 x 10.sup.-5), knee flexors strength (MD = 2.03 [0.66, 3.41], p = 0.005), knee extensors strength (MD = 1.80 [0.65, 2.94], p = 0.003), and functional-reach (cm) (MD = 3.74 [0.68, 6.80], p = 0.018), with large effect sizes (Î·.sup.2 = 0.17-0.42), than those in the CON group after the intervention. Conclusions Older adults with knee OA in the CRE group exhibited superior muscle strength, health conditions, and functional fitness improvements after the 12-week computer-aided rowing exercise program than those receiving the conventional exercise approach. Trial registration The Institutional Review Board of the Taipei Medical University approved the study protocol (no. N201908020, 27/05/2020) and retrospectively registered at ClinicalTrials.gov (trial registry no. NCT04919486, 09/06/2021). Keywords: Older adults, Computer-aided system, Rowing exercise, WOMAC, Lower joint impact, Osteoarthritis